U.S. multinationals’ foreign cash holdings: an empirical estimate and the impact of the tax cuts and jobs act of 2017 on the value of foreign cash - Campbell, John L.; Dhaliwal, Dan S.; Krull, Linda K.; Schwab, Casey M. (Review of Accounting Studies, 2025)
Abstract We use publicly available information to estimate the country location of multinational firms’ cash holdings, examine why investors discount the value of cash held overseas, and examine whether that discount changes after the Tax Cuts and Jobs Act (TCJA) of 2017. We provide three main results. First, our firm-year foreign cash estimates are reasonably accurate, evidenced by high correlations with simulated data and proprietary country-level data, high adjusted R 2 when explaining a firm’s total cash holdings, and the ability to replicate prior findings. Second, we demonstrate that investors value foreign cash holdings more negatively than domestic cash holdings when the cash is held in high agency-cost countries. Finally, we find that investors no longer appear to discount foreign cash after the TCJA, when the U.S. moved from a worldwide to a quasi-territorial taxation system.